2006
DOI: 10.1007/11733836_63
|View full text |Cite
|
Sign up to set email alerts
|

Communication-Efficient Implementation of Range-Joins in Sensor Networks

Abstract: In this article, we consider energy-efficient implementation of the SQL join operation in sensor databases, when the join selection condition is a range predicate. Apart from two simple approaches, we propose distributed hash-join and index-join algorithms for implementation of range-join operations in sensor networks. Through extensive simulations, we show that hash-join as well as index-join approaches significantly outperform the simple approaches, even for moderately sized networks. Our experiments also re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 14 publications
0
45
0
Order By: Relevance
“…In this case, a node in the geographical centre of a triangle formed by two regions and the base-station is chosen as the processing processing node. Similarly, if the data sources are scattered throughout the network, Pandit and Gupta propose to choose a random node using the hash of the join key, as the processing node [9]. Stern et al propose Continuous Join Filtering (CJF) -a twophase approach where first summaries of static and dynamic attributes of all nodes in the network are collected, then the base-station uses these summaries to choose candidates for the join [10].…”
Section: A Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, a node in the geographical centre of a triangle formed by two regions and the base-station is chosen as the processing processing node. Similarly, if the data sources are scattered throughout the network, Pandit and Gupta propose to choose a random node using the hash of the join key, as the processing node [9]. Stern et al propose Continuous Join Filtering (CJF) -a twophase approach where first summaries of static and dynamic attributes of all nodes in the network are collected, then the base-station uses these summaries to choose candidates for the join [10].…”
Section: A Related Workmentioning
confidence: 99%
“…An alternative is processing on a random node in the network. The node could be chosen using, for example, a hash function [8], [9]. However, it has been shown that processing data on a random node leads to higher network traffic than processing at-the-base [11].…”
Section: Evaluation a Setupmentioning
confidence: 99%
“…[14] processes the join on the path between the input data and the query issuer. [15] extends the approach for range queries. Coman et al [8] present (among other methods) a "mediated join" which computes the result at a central location inside the network.…”
Section: Related Workmentioning
confidence: 99%
“…Differently from us, they do not investigate the allocation of memory at the nodes in the join region and the synchronized data flow. Pandit and Gupta [11] propose two algorithms for in-network processing of the range-join operator. Both works [4,11] consider that the optimal join location is the weighted centroid of the triangle ABO.…”
Section: Related Workmentioning
confidence: 99%
“…Bonfils and Bonnet [3] investigate placing a correlation operator at a node in the network. Pandit and Gupta [11] propose two algorithms for processing a range-join operator in the network and Yu at al. [16] propose an algorithm for processing equi-joins.…”
Section: Introductionmentioning
confidence: 99%